Islamic Republic of Mauritania : Third Review Under the Three-Year Extended Credit Facility Arrangement: Staff Report; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Islamic Republic of Mauritania's macroeconomic developments have remained broadly positive, despite high international fuel and food prices and the near-term drought impact. Supported by a rapid growth in manufacturing industries, non-oil output is expected to grow by 4.8 percent in 2011 despite the drought-related downturn in agricultural production. A low price pass-through and a prudent monetary policy helped contain inflation. Booming mining exports helped narrow the current account deficit and boost foreign exchange reserves to unprecedented levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet